Draft Annual Plan 1988-89 Volume : VI General Areas Government of Assam - Planning Commission (Planning Commission, 1988)
The School Health Services scheme providing facilities for examination of Health of School students continued to function. Activities under the Health Education scheme were also continued. The scheme for prevention of "Food adulteration" was strengthened by of appointment of more inspecting staff. The "Drugs Control" administration has further been strengthened. "Births and Deaths Registration" act was under implementation during the period.
Government of Assam, Planning and Development Department